Positive electrode material, positive electrode plate, battery and electric equipment
By covering the modified solid electrolyte xA·(1-x-y) LIPON·yM on the positive electrode material of the lithium-ion battery, the interface side reaction problem between the positive electrode active material of the lithium-ion battery and the electrolyte is solved, and the service life and electrochemical performance of the battery are improved.
Patent Information
- Application Number
- CN202411747898.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-04-04
AI Technical Summary
The interface side reaction between the positive electrode active material and the electrolyte of the existing lithium-ion battery leads to a short battery life and insufficient conductivity and stability of the traditional cladding materials.
Modified solid electrolyte xA·(1-x-y)LIPON·yM, where A includes C, Si, SiC and GaN, and M includes Mg, Ti, Mo, La, Nb, V and Te, the modified solid electrolyte is prepared by mixing these materials and wrapped around the outer surface of the active material to improve the transmission rate and stability of electrons and lithium ions.
It effectively inhibits the interface side reaction between active materials and electrolyte, improves the transmission rate of electrons and lithium ions, extends the service life of the battery, and improves the electrochemical performance of the battery.
Smart Images

Figure CN119764369A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and in particular to a positive electrode material, a positive electrode sheet, a battery and an electrical device. Background Art
[0002] In order to extend the service life of lithium-ion batteries, one of the measures is to alleviate the interface side reactions between the positive electrode active material and the electrolyte. In traditional technology, other materials are usually coated on the surface of the positive electrode active material to reduce the direct contact between the positive electrode active material and the electrolyte. However, the common other materials used for coating have poor lithium ion conductivity or low electronic conductivity, and poor stability and electrochemical performance of the positive electrode active material. Summary of the invention
[0003] The present invention aims to solve at least one of the technical problems existing in the prior art. To this end, one purpose of the present invention is to provide a positive electrode material that improves the stability of the active material, comprehensively improves the transmission rate of electrons and lithium ions, prolongs the service life of the battery and improves the electrochemical performance of the battery.
[0004] The second objective of the present invention is to provide a positive electrode sheet.
[0005] The third object of the present invention is to provide a battery.
[0006] A fourth object of the present invention is to provide an electrical device.
[0007] The positive electrode material according to the embodiment of the first aspect of the present invention includes: an active material and a modified solid electrolyte, wherein the modified solid electrolyte is wrapped on the outer surface of the active material, and the chemical formula of the modified solid electrolyte is xA·(1-xy)LIPON·yM, wherein A includes at least one of C, Si, SiC and GaN, and M includes at least one of Mg, Ti, Mo, La, Nb, V and Te.
[0008] According to the positive electrode material of the embodiment of the first aspect of the present invention, by mixing substance A, metal M and LIPON to prepare a modified solid electrolyte, A and metal M synergistically modify the LIPON-type solid electrolyte to comprehensively improve the electron and lithium ion transmission rate, and improve its stability, which is beneficial to the use of positive electrode materials and batteries. The C, Si or Ga atoms with good conductivity in A form chemical bonds with the N atoms of LiPON to improve the stability of the LIPON-type modified solid electrolyte to water, and also improve the conductivity.
[0009] According to some embodiments of the present invention, the M includes at least one of Ti, Mo and Nb.
[0010] According to some embodiments of the present invention, the x satisfies: 0<x<1; and / or, the y satisfies: 0.0001<y<0.03.
[0011] According to some embodiments of the present invention, the x further satisfies: 0.1<x<0.4; and / or, the y further satisfies: 0.0005<y<0.02.
[0012] According to some embodiments of the present invention, the primary particle size of the positive electrode material is D1, and the specific surface area is S, wherein D1 and S respectively satisfy: 0.1 μm ≤ D1 ≤ 10 μm, 0.5 μm 2 / g≤S≤18m 2 / g.
[0013] According to some embodiments of the present invention, the thickness of the modified solid electrolyte wrapped on the active material is W, wherein W satisfies: 1 nm≤W≤20 nm.
[0014] According to some embodiments of the present invention, the active material includes at least one of lithium iron manganese phosphate, lithium iron oxide, ternary material, lithium-rich manganese, lithium manganate, lithium cobalt oxide, lithium vanadium phosphate and lithium nickel oxide.
[0015] The positive electrode sheet according to the second embodiment of the present invention comprises: a current collector; a positive electrode material layer, wherein the positive electrode material layer is formed by applying the positive electrode material according to the first embodiment on at least one side of the current collector in the thickness direction.
[0016] The battery according to the third aspect of the present invention comprises the positive electrode material according to the first aspect, or the positive electrode sheet according to the second aspect.
[0017] The electrical equipment according to the fourth embodiment of the present invention comprises the battery described in the third embodiment.
[0018] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which: Figure 1 According to the present invention, LiMn 0.6 Fe 0.4 SEM image of PO4@[0.2C•0.792LIPON•0.008Nb]; Figure 2 According to the present invention, LiMn0.6 Fe 0.4 X-ray diffraction pattern of PO4@[0.2C•0.792LIPON•0.008Nb]; Figure 3 According to the present invention, LiMn 0.6 Fe 0.4 XPS narrow spectrum of N1s of PO4@[0.2C•0.792LIPON•0.008Nb]; Figure 4 According to the present invention embodiment 2, Li 1.2 Ni 0.13 Co 0.13 Mn 0.54 The XPS narrow spectrum of N1s of O2@[0.3SiC•0.69LIPON•0.01Nb]; Figure 5 1 is a graph of the discharge specific capacity at 0.5C according to Example 1 and Example 4 of the present invention; Figure 6 Graph showing the discharge capacity at different rates according to Example 1 and Example 5 of the present invention. DETAILED DESCRIPTION
[0020] The embodiments of the present invention are described in detail below. The embodiments described with reference to the accompanying drawings are exemplary. Figure 1-Figure 6 The positive electrode material according to the first embodiment of the present invention is described in detail.
[0021] The positive electrode material according to the first embodiment of the present invention includes an active material and a modified solid electrolyte.
[0022] Specifically, the modified solid electrolyte is wrapped on the outer surface of the active material, and the chemical formula of the modified solid electrolyte is xA·(1-xy)LIPON·yM, wherein A includes at least one of C, Si, SiC and GaN, and M includes at least one of Mg, Ti, Mo, La, Nb, V and Te.
[0023] For example, when the positive electrode material is used for the positive electrode sheet, the positive electrode material layer is located on at least one side surface of the current collector in the thickness direction. The positive electrode material layer can be formed by coating the positive electrode material. The core of the positive electrode material is an active material, and the shell is a modified solid electrolyte, that is, the positive electrode material is obtained after the modified solid electrolyte completely wraps the outer surface of the positive electrode material. The modified solid electrolyte can be prepared by mixing A, LIPON and M in a specified molar ratio. The molar ratio of A, LIPON and M is x: (1-xy): y. Among them, LIPON generally refers to "lithium phosphorus oxynitride". For example, the composite of active material and modified solid electrolyte can be expressed as Q@[xA·(1-xy)LIPON·yM], where Q is the active material.
[0024] Therefore, when the positive electrode material is used in the positive electrode sheet, the modified solid electrolyte can effectively inhibit the interfacial side reaction between the active material and the electrolyte and improve the electron and lithium ion transmission rate. The C, Si or Ga atoms with good conductivity in A form chemical bonds with the N atoms of LiPON to improve the stability of the LIPON-type modified solid electrolyte to water, and also improve the conductivity. Moreover, doping with trace amounts of metal elements (M) can improve the lithium ion transmission rate of the LIPON-type modified solid electrolyte. The synergistic modification of the LIPON-type solid electrolyte by A and metal M can comprehensively improve the electron and lithium ion transmission rate and improve its stability. Among them, the chemical bonds formed by C, Si or Ga atoms and the N atoms of LiPON can be characterized according to the photoelectron spectroscopy (XPS), and the corresponding bond generation can be obtained by peak analysis of the narrow spectrum of the N1s element. The modified LIPON-type solid electrolyte is coated on the surface of the active material. Compared with the traditional thin film solid electrolyte layer coating the positive electrode active material, the present application improves the stability of the active material, comprehensively improves the transmission rate of electrons and lithium ions, extends the service life of the battery and improves the electrochemical performance of the battery.
[0025] According to the positive electrode material of the embodiment of the first aspect of the present invention, by mixing substance A, metal M and LIPON to prepare a modified solid electrolyte, A and metal M synergistically modify the LIPON-type solid electrolyte to comprehensively improve the electron and lithium ion transmission rate, and improve its stability, which is beneficial to the use of positive electrode materials and batteries. The C, Si or Ga atoms with good conductivity in A form chemical bonds with the N atoms of LiPON to improve the stability of the LIPON-type modified solid electrolyte to water, and also improve the conductivity.
[0026] Preferably, M includes at least one of Ti, Mo and Nb. That is, metal A is composed of at least one of Ti, Mo and Nb. M composed of the above metals can further improve the lithium ion transmission rate of the LIPON type modified solid electrolyte. In addition, titanium Ti can improve the strength and corrosion resistance of the material. Molybdenum Mo can enhance the high temperature strength and creep resistance of the material. Niobium Nb can improve the toughness and fatigue resistance of the material.
[0027] According to some embodiments of the present invention, x satisfies: 0<x<1. And / or, y satisfies: 0.0001<y<0.03. For example, in terms of molar percentage, the molar percentage of A is 0-100% (excluding the endpoint value), and the molar percentage of M is 0.01%-3% (excluding the endpoint value). In this way, the mixing ratio of A, M and LIPON in the modified solid electrolyte is reasonably set, which is conducive to the performance of the modified solid electrolyte, further extending the service life of the battery and improving the electrochemical performance of the battery.
[0028] Preferably, x satisfies: 0.1<x<0.4. And / or, y satisfies: 0.0005<y<0.02. For example, taking A as an example, combined with the measurement results in Table 1, when carbon powder, Li3PO4 and Nb metal powder are mixed in a molar ratio of 10:89.2:0.8 to prepare a modified solid electrolyte, the 100-cycle capacity retention rate of the battery will decrease. When carbon powder, Li3PO4 and Nb metal powder are mixed in a molar ratio of 41:58.2:0.8 to prepare a modified solid electrolyte, the 2C relative 1C capacity retention rate of the battery will decrease. In other words, when x satisfies: 0.1<x<0.4, the 100-cycle capacity retention rate and 2C relative 1C capacity retention rate of the prepared battery are both high, and the overall performance of the battery is excellent.
[0029] According to some embodiments of the present invention, the primary particle size of the positive electrode material is D1, and the specific surface area is S, wherein D1 and S respectively satisfy: 0.1 μm ≤ D1 ≤ 10 μm, 0.5 μm 2 / g≤S≤18m 2 / g.
[0030] For example, when the primary particle size D1 is not less than 0.1 μm, this helps to ensure the stability of the positive electrode material during preparation and subsequent processing. If the particle size is too small, for example, less than 0.1 μm, the particles may agglomerate during the synthesis process due to excessive surface energy. In practical applications, particles that are too small may block the pores of the electrode and affect ion transport. A particle size D1 of no more than 10 μm can ensure that the positive electrode material has a sufficiently large specific surface area to achieve good ion conduction. If the particle size is too large, the specific surface area will decrease accordingly, and the path for ion transport in the positive electrode material will become longer, which will increase the resistance to ion transport.
[0031] The specific surface area S is not less than 0.5m 2 / g can provide sufficient adsorption and desorption sites for ions. In positive electrode materials, ion conduction is often achieved through the adsorption-desorption process on the electrolyte surface and the jumping between particles. Sufficient specific surface area can ensure that there are enough ion conduction channels. When the specific surface area S does not exceed 18m 2 / g, too high a specific surface area may cause the positive electrode material to absorb too much impurities or moisture, affecting its performance. For example, in a solid electrolyte containing an oxide, too large a specific surface area may absorb moisture from the air, causing the positive electrode material to undergo a hydrolysis reaction, destroying its crystal structure, and thus reducing its ion conductivity.
[0032] According to some embodiments of the present invention, the thickness of the modified solid electrolyte wrapped on the active material is W, wherein W satisfies: 1nm≤W≤20nm. For example, when the thickness of the modified solid electrolyte is less than 1nm, the thickness of the modified solid electrolyte is small, which is not conducive to uniform formation on the outer peripheral surface of the active material. Moreover, the electrolyte is easily in contact with the active material through the modified solid electrolyte, reducing the barrier effect of the modified solid electrolyte. When the thickness of the modified solid electrolyte is greater than 20nm, the thickness of the modified solid electrolyte is too large, which will affect the transmission of electrons and lithium ions, and will also reduce the discharge specific capacity. Thus, by setting the thickness of the modified solid electrolyte to 1nm~20nm, the thickness of the modified solid electrolyte is moderate, which is conducive to the formation of the modified solid electrolyte while also being conducive to the use of the positive electrode material.
[0033] According to some embodiments of the present invention, the active material includes an active material, and the active material includes at least one of lithium iron manganese phosphate, lithium iron lithium oxide, ternary material, lithium-rich manganese, lithium manganate, lithium cobalt oxide, lithium vanadium phosphate and lithium nickel oxide.
[0034] For example, in terms of energy density, lithium manganese iron phosphate combines the stability of lithium iron phosphate with the high voltage characteristics brought by manganese. Its voltage platform is higher than that of lithium iron phosphate, which improves the energy density at the same power. x Co y Mn 1-x-yO2) can flexibly control the energy density by adjusting the ratio of nickel, cobalt and manganese. The increase in nickel content can significantly increase the reversible capacity of the material, thereby increasing the energy density. Lithium-rich manganese (such as xLi2MnO3・(1-x)LiMO2, M=Ni, Co, Mn, etc.) has a higher theoretical specific capacity. Lithium cobalt oxide (LiCoO2) is an early and widely used positive electrode material with a high energy density. In terms of cycle life, lithium iron phosphate (LiFePO4) has an excellent cycle life. Lithium manganese oxide (LiMn2O4) can also show good cycle performance under appropriate working conditions, such as in a lower temperature and voltage range. In terms of safety, both lithium iron phosphate and lithium manganese iron phosphate have good thermal and chemical stability. Under extreme conditions such as high temperature and overcharge, thermal runaway is not likely to occur. For lithium manganese oxide, the safety is relatively high within the normal operating temperature and voltage range. Its three-dimensional lithium ion channel structure can alleviate the stress generated during the lithium ion insertion / extraction process to a certain extent, reducing the possibility of safety problems caused by structural damage. Lithium manganate has a three-dimensional lithium ion channel due to its spinel structure, which makes the lithium ion diffusion coefficient relatively high and can achieve rapid charge and discharge. In other words, the positive electrode material of the present application can adopt a variety of different active materials, and has a wide range of applications. Moreover, the above-mentioned multiple active materials have different performance advantages.
[0035] A method for preparing a positive electrode material according to the first embodiment of the present invention comprises the following steps: A, LIPON and M powders are mixed evenly, and the modified solid electrolyte is prepared by hot pressing in an inert gas protective atmosphere.
[0036] The modified solid electrolyte is deposited onto the surface of the active material by magnetron sputtering to prepare the positive electrode material.
[0037] That is to say, the modified solid electrolyte can be prepared under preset conditions by uniformly mixing the three components included in the modified solid electrolyte. Then, the positive electrode material is prepared by applying the modified solid electrolyte on the surface of the active material. The preparation method is simple, with few steps, which is conducive to the processing and use of the positive electrode material.
[0038] According to some embodiments of the present invention, the hot pressing in the above steps specifically includes: The temperature is raised to a preset temperature at a first preset pressure, and maintained at a preset time at a second preset pressure, the heating rate is k, the first preset pressure is P1, the preset temperature is T, the second preset pressure is P2, and the preset time is t, wherein k, P1, T, P2, and t respectively meet the following conditions: 5℃•min -1 ≤k≤10℃•min -1, 8mPa≤P1≤16mPa, 30min≤T≤60min, 18mPa≤P2≤30mPa, 500℃≤t≤1200℃. That is to say, in the hot pressing process of the above steps, when the temperature is lower than the preset hot pressing temperature (ie, the preset temperature) during the heating process, the pressure applied is 8mPa-16mPa, and after heating to the preset hot pressing temperature, the pressure applied is 18mPa-30mPa, and the temperature is kept for 30min-60min. Among them, the hot pressing temperature (ie, the preset temperature) is selected according to the material, ranging from 500℃-1200℃, and the heating rate is 5℃·min -1 -10℃·min -1 Such a configuration is conducive to the agglomeration of A, LiPON and M powders, and the formation of chemical bonds between the C, Si or Ga atoms in A and the N atoms in LiPON, thereby facilitating the preparation of the modified solid electrolyte and the performance of the positive electrode material. Optionally, the purity of A, Li3PO4 and M metal powders should be greater than 99.9%.
[0039] According to some embodiments of the present invention, the particle size of the M powder is D2, and D2 satisfies: 100nm≤D2≤800nm. In this way, the particle size of the metal powder is reasonably set, which is beneficial for the metal element (M) to improve the lithium ion transmission rate of the LIPON-type modified solid electrolyte, and is also beneficial for the metal M and A to synergistically modify the LIPON-type solid electrolyte to comprehensively improve the electron and lithium ion transmission rate. In addition, it is beneficial for the M powder to be evenly mixed with A and LIPON, and can be evenly distributed on the surface of the active material through magnetron sputtering.
[0040] According to some optional embodiments of the present invention, the above-mentioned uniform mixing of A, LIPON and M powders specifically includes: The A, LIPON and M powders are evenly mixed by ball milling for 12h-48h, preferably 24h-36h. Ball milling within the above-specified time can make the mixing of A, LIPON and M powders more uniform, and the mixing operation is simple, which is beneficial to the preparation of positive electrode materials and improves processing efficiency.
[0041] According to some embodiments of the present invention, the modified solid electrolyte is deposited onto the surface of the active material by magnetron sputtering, specifically comprising: The film is coated by a vibration sputtering method in a mixed atmosphere of argon and nitrogen, with an argon flow rate of 5 sccm to 15 sccm, a nitrogen flow rate of 20 sccm to 40 sccm, a sputtering power of 10 W to 200 W, a modified solid electrolyte temperature controlled at 20° C. to 300° C., and a sputtering time of 60 min to 600 min.
[0042] With such a configuration, sputtering coating is performed under the above-defined conditions, and an electrolyte layer can be uniformly formed on the surface of the active material, which is beneficial to the preparation of the electrolyte layer. The vibration sputtering coating method is adopted, and the vibration frequency or amplitude of the sample table vibration screen is adjusted to make the primary particles in a suspended state, ensuring that the surface of the powder primary particles is uniformly coated with the modified solid electrolyte film, so as to facilitate the performance of the modified solid electrolyte. In addition, the vibration sputtering coating method is mainly to ensure that the modified solid electrolyte coated on the active material is evenly distributed and to ensure that the thickness of the modified solid electrolyte coated between each particle is consistent.
[0043] The positive electrode sheet according to the second embodiment of the present invention comprises a current collector and a positive electrode material layer, wherein the positive electrode material layer is formed by applying the positive electrode material according to the first embodiment on at least one side surface of the current collector in the thickness direction.
[0044] The positive electrode sheet according to the second embodiment of the present invention adopts the above-mentioned positive electrode material, which improves the performance of the electrode sheet and prolongs the service life of the positive electrode sheet.
[0045] The battery according to the third aspect of the present invention comprises the positive electrode material according to the first aspect, or the positive electrode sheet according to the second aspect.
[0046] The battery according to the third aspect of the present invention adopts the above-mentioned positive electrode material, which improves the performance of the battery and prolongs the service life of the battery.
[0047] An electrical device according to an embodiment of the fourth aspect of the present invention comprises the battery of the embodiment of the third aspect.
[0048] According to the fourth aspect of the present invention, the electric equipment of the embodiment improves the performance of the electric equipment by using the above-mentioned battery. For example, the electric equipment includes vehicles, aircraft, ships, computers, energy storage cabinets, etc.
[0049] The embodiments of the present invention are described in detail below. It should be noted that the embodiments described below are exemplary and are only used to explain the present invention, and cannot be interpreted as limiting the present invention. In addition, if not explicitly stated, all reagents used in the following embodiments are commercially available, or can be synthesized according to this article or known methods, and the reaction conditions not listed are also easily available to those skilled in the art.
[0050] The battery of the present invention is described by means of exemplary specific embodiments combined with comparative examples. The following tests are conducted on the battery performance of the battery (eg, lithium ion button half-cell) made of the positive electrode materials of the embodiments and comparative examples.
[0051] Example 1 LiMn0.6 Fe 0.4 Preparation of PO4@[0.2C•0.792LIPON•0.008Nb]: Carbon powder with a particle size of 200 nm, Li3PO4 and Nb metal powder were ground in a mortar at a molar ratio of 20:79.2:0.8 for 32 h, mixed evenly, and hot pressed in an argon protective atmosphere to prepare the required modified solid electrolyte. The hot pressing temperature was 700°C, and the pressure applied was 10 mPa when the temperature was below 700°C during the heating process. After the temperature was raised to the preset temperature, a pressure of 25 mPa was applied, and the temperature was kept for 40 minutes, with a heating rate of 8°C•min -1 .
[0052] The modified solid electrolyte was heated in a mixed atmosphere of argon and nitrogen over LiMn 0.6 Fe 0.4 The surface of PO4 was sputtered to obtain the positive electrode material. The parameters of the sputtering coating were argon flow rate of 10sccm, nitrogen flow rate of 30sccm, sputtering power of 100W, sample temperature of 80℃, sputtering time of 100min, and the positive electrode material LiMn was obtained. 0.6 Fe 0.4 PO4@[0.2C•0.792LIPON•0.008Nb]. Characterization test: such as Figure 1 As shown, LiMn 0.6 Fe 0.4 The primary particle size of PO4@[0.2C•0.792LIPON•0.008Nb] is 150nm. LiMn 0.6 Fe 0.4 The specific surface area of PO4@[0.2C•0.792LIPON•0.008Nb] is 15.3 m 2 / g. Figure 2 As shown, it can be seen from X-ray diffraction (XRD) that LiMn 0.6 Fe 0.4 The diffraction peak of PO4@[0.2C•0.792LIPON•0.008Nb] corresponds well to the lithium manganese iron phosphate standard card, and the modified solid electrolyte does not change the crystal structure of lithium manganese iron phosphate. Figure 3 LiMn 0.6 Fe 0.4XPS narrow spectrum of N1s for PO4@[0.2C•0.792LIPON•0.008Nb]. For LIPON, the P-N<P has a binding energy of 397.8 eV, P=N-P has a binding energy of 399.3 eV, and the C-N bond formed by C and LIPON has a binding energy of 400.4 eV.
[0053] Assembly of lithium-ion coin half-cells: LiMn prepared in Example 1 0.6 Fe 0.4 The cathode material PO4@[0.2C•0.792LIPON•0.008Nb], conductive agent carbon nanotubes, and polyvinylidene fluoride were mixed evenly in N-methylpyrrolidone solvent at a mass ratio of 100:2:2.5 to obtain the cathode slurry. The solid content of the cathode slurry was 55%. The cathode slurry was coated on carbon-coated aluminum foil to obtain the cathode sheet, and the lithium-ion coin half-cells were assembled with the cathode sheet. The lithium-ion coin half-cells prepared in this example were charged and discharged in a constant current and constant voltage mode at a rate of 0.5C for 100 cycles, and the voltage range was 2.0 - 4.3V. The measured cyclic discharge specific capacity was recorded in Figure 3 , and the capacity retention rate after 100 cycles was recorded in Table 1. In the voltage range of 2.0 - 4.3V, the discharge specific capacity at different rates was tested, and the capacity retention rate of 2C relative to 0.1C was recorded in Table 1.
[0054] Example 2 Li 1.2 Ni 0.13 Co 0.13 Mn 0.54 Preparation of LiNiCoMnO2@[0.3SiC•0.69LIPON•0.01Nb]: SiC powder with a particle size of 300 nm, Li3PO4, and Nb metal powder were ground in a mortar for 32 h according to a molar ratio of 30:69:1 and mixed evenly. The required modified solid electrolyte was prepared by hot pressing in a protective atmosphere of argon. Among them, the hot pressing temperature was 1000°C. When the temperature was below 1000°C during the heating process, the applied pressure was 12 mPa. After the temperature was raised to the preset temperature, the pressure was 28 mPa, and it was kept warm for 60 min. The heating rate was 10°C•min -1 .
[0055] The modified solid electrolyte was placed in a mixed atmosphere of argon and nitrogen with Li 1.2 Ni 0.13 Co 0.13 Mn 0.54Sputtering coating is carried out on the O2 surface to obtain the cathode material. Among them, the parameters of sputtering coating are as follows: the flow rate of argon is 12 sccm, the flow rate of nitrogen is 28 sccm, the sputtering power is 150 W, the temperature of the sample is 100 °C, and the sputtering time is 200 min, obtaining the cathode material Li 1.2 Ni 0.13 Co 0.13 Mn 0.54 O2@[0.3SiC•0.69LIPON•0.01Nb].
[0056] Characterization test: It can be obtained through scanning electron microscope test that the primary particle size of Li 1.2 Ni 0.13 Co 0.13 Mn 0.54 O2@[0.3SiC•0.69LIPON•0.01Nb] is 180 nm. It can be obtained through nitrogen (N2) adsorption and desorption test that the specific surface area of Li 1.2 Ni 0.13 Co 0.13 Mn 0.54 O2@[0.3SiC•0.69LIPON•0.01Nb] is 3.1 m 2 / g. It can be seen through X-ray diffraction (XRD) that the diffraction peaks of Li 1.2 Ni 0.13 Co 0.13 Mn 0.54 O2@[0.3SiC•0.69LIPON•0.01Nb] correspond well with the standard card of lithium iron manganese phosphate, and the modified solid electrolyte does not change the crystal structure of lithium-rich manganese. Figure 4 For Li 1.2 Ni 0.13 Co 0.13 Mn 0.54 The narrow XPS spectrum of N1s of O2@[0.3SiC•0.69LIPON•0.01Nb] shows that at the binding energy of 397.8 eV is P-N<P in LIPON, at the binding energy of 399.3 eV in LIPON is P=N-P, at the binding energy of 400.4 eV is the C-N bond formed by C and LIPON, and at 398.28 eV is the Si-N bond formed by Si and LIPON.
[0057] Assembly of lithium-ion coin half-cells: The Li prepared in Example 2 1.2 Ni 0.13 Co 0.13 Mn 0.54O2@[0.3SiC•0.69LIPON•0.01Nb] positive electrode material, conductive agent carbon nanotubes and polyvinylidene fluoride are mixed in N-methylpyrrolidone solvent at a mass ratio of 100:2:2.5 to obtain a positive electrode slurry. The solid content of the positive electrode slurry is 55%. The slurry is coated on a carbon-coated aluminum foil to obtain a positive electrode sheet, and the positive electrode sheet is used to assemble a lithium-ion button half-cell. The lithium-ion button half-cell prepared in this embodiment is charged and discharged at a constant current and constant voltage for 100 cycles at a rate of 0.5C, and the voltage range is 2.0-4.5V. The measured cyclic discharge specific capacity and the capacity retention rate of 100 cycles are recorded in Table 1. In the voltage range of 2.0-4.5V, the discharge specific capacity at different rates is tested, and the capacity retention rate of 2C relative to 0.1C is recorded in Table 1.
[0058] Example 3 Preparation of LiFePO4@[0.25SiC•0.74LIPON•0.01Mo]: SiC powder with a particle size of 500 nm, Li3PO4 and Nb metal powder were ground in a mortar at a molar ratio of 25:74:1 for 26 h, mixed evenly, and hot pressed in an argon protective atmosphere to prepare the required modified solid electrolyte. The hot pressing temperature was 1000°C, and the pressure applied was 10mPa when the temperature was below 1000°C during the heating process. After the temperature was raised to the predetermined hot pressing temperature, a pressure of 27mPa was applied, and the temperature was kept for 40 min, with a heating rate of 15°C.
[0059] The modified solid electrolyte was sputtered on the surface of LiFePO4 in a mixed atmosphere of argon and nitrogen. The parameters of the sputtering coating were 15sccm of argon gas flow, 30sccm of nitrogen gas flow, 140W of sputtering power, 140℃ of sample temperature, and 200min of sputtering time, and the positive electrode material LiFePO4@[0.25SiC•0.74LIPON•0.01Mo] was obtained.
[0060] Characterization test: Scanning electron microscopy test showed that the primary particle size of LiFePO4@[0.25SiC•0.74LIPON•0.01Mo] was 240nm. Nitrogen (N2) adsorption and desorption test showed that the specific surface area of LiFePO4@[0.25SiC•0.74LIPON•0.01Mo] was 10.4 m 2 / g. X-ray diffraction (XRD) shows that the diffraction peak of LiFePO4@[0.25SiC•0.74LIPON•0.01Mo] corresponds well to the lithium manganese iron phosphate standard card, and the modified solid electrolyte does not change the crystal structure of lithium iron phosphate.
[0061] Assembly of lithium-ion button half-cell: The LiFePO4@[0.25SiC•0.74LIPON•0.01Mo] positive electrode material prepared in Example 3, conductive agent carbon nanotubes and polyvinylidene fluoride were mixed in N-methylpyrrolidone solvent at a mass ratio of 100:2:2.5 to obtain a positive electrode slurry, the solid content of the positive electrode slurry was 55%, the positive electrode slurry was coated on a carbon-coated aluminum foil to obtain a positive electrode sheet, and the positive electrode sheet was used to assemble a lithium-ion button half-cell. The lithium-ion button half-cell prepared in this example was charged and discharged at a constant current and constant voltage at a rate of 0.5C for 100 cycles, and the voltage range was 2.5-3.65V. The measured cycle discharge specific capacity and the capacity retention rate of 100 cycles are recorded in Table 1. In the voltage range of 2.5-3.65V, the discharge specific capacity at different rates was tested, and the capacity retention rate of 2C relative to 0.1C is recorded in Table 1.
[0062] Example 4 The method described in Example 1 was followed, except that the positive electrode material (LiMn 0.6 Fe 0.4 PO4@[0.1C•0.879LIPON•0.021Nb]) in different proportions. The assembly of lithium-ion button half-cell is the same as in Example 1.
[0063] Characterization test: LiMn can be obtained by scanning electron microscopy test 0.6 Fe 0.4 The primary particle size of PO4@[0.1C•0.879LIPON•0.021Nb] is 160 nm. The specific surface area is 14.2 m 2 / g, XRD shows that the diffraction peak of the positive electrode material corresponds well to the lithium iron manganese phosphate standard card, indicating that the modified solid electrolyte does not change the crystal structure of lithium iron manganese phosphate.
[0064] The discharge capacity at different rates was recorded in Figure 6 The capacity retention rate of 2C relative to 0.1C is recorded in Table 1. Figure 5 The test results of the discharge specific capacity of the lithium-ion batteries prepared in Examples 1 and 4 after 100 cycles are shown. Since the content of C in the modified solid electrolyte in Example 4 is reduced, the number of chemical bonds formed with the N atoms of LiPON is relatively small, and its stability is poor, so that the discharge specific capacity of Example 4 decays faster than that of Example 1 during the cycle.
[0065] Example 5 The method described in Example 1 was followed, except that the positive electrode material (LiMn 0.6 Fe 0.4PO4@[0.41C•0.5895LIPON•0.0005Nb]) in different proportions. The assembly of lithium-ion button half-cell is the same as in Example 1.
[0066] Characterization test: LiMn can be obtained by scanning electron microscopy test 0.6 Fe 0.4 The primary particle size of PO4@[0.41C•0.5895LIPON•0.0005Nb] is 130 nm. The specific surface area is 16.5 m 2 / g, XRD shows that the diffraction peak of the positive electrode material corresponds well to the lithium iron manganese phosphate standard card, indicating that the modified solid electrolyte does not change the crystal structure of lithium iron manganese phosphate.
[0067] The discharge capacity at different rates was recorded in Figure 6 The capacity retention rate of 2C relative to 0.1C is recorded in Table 1. Figure 6 The test results of the discharge specific capacity of the lithium-ion batteries prepared in Example 1 and Example 5 at different rates are shown. Since the content of C in the modified solid electrolyte in Example 5 is relatively large and the content of LiPON is relatively small, the lithium ion transmission channels in the modified solid electrolyte are reduced, making the rate performance of Example 5 worse than that of Example 1.
[0068] Example 6 The method described in Example 1 was followed, except that the positive electrode material (LiMn 0.6 Fe 0.4 PO4@[0.005C•0.9949LIPON•0.0001Nb]) in different proportions. The assembly of lithium-ion button half-cell is the same as in Example 1.
[0069] Characterization test: LiMn can be obtained by scanning electron microscopy test 0.6 Fe 0.4 The primary particle size of PO4@[0.005C•0.9949LIPON•0.0001Nb] is 137 nm. The specific surface area is 15.1 m 2 / g, XRD shows that the diffraction peak of the positive electrode material corresponds well to the lithium iron manganese phosphate standard card, indicating that the modified solid electrolyte does not change the crystal structure of lithium iron manganese phosphate.
[0070] The capacity retention rate of 100 cycles and the capacity retention rate of 2C relative to 0.1C are recorded in Table 1. Since the content of C in the modified solid electrolyte in Example 6 is low, the number of chemical bonds formed with the N atoms of LiPON is small and its stability is poor, so that the discharge specific capacity decay in the cycle of Example 6 is faster than that in Example 4.
[0071] Example 7 The method described in Example 1 was followed, except that the positive electrode material (LiMn 0.6 Fe 0.4 The proportions of the components in PO4@[0.96C•0.01LIPON•0.03Nb] are different. The assembly of lithium-ion button half-cell is the same as in Example 1.
[0072] Characterization test: LiMn can be obtained by scanning electron microscopy test 0.6 Fe 0.4 The primary particle size of PO4@[0.96C•0.01LIPON•0.03Nb] is 133 nm. The specific surface area is 14.5 m 2 / g, XRD shows that the diffraction peak of the positive electrode material corresponds well to the lithium iron manganese phosphate standard card, indicating that the modified solid electrolyte does not change the crystal structure of lithium iron manganese phosphate.
[0073] The capacity retention rate of 100 cycles and the capacity retention rate of 2C relative to 0.1C are recorded in Table 1. Since the content of C in the modified solid electrolyte in Example 7 is high and the proportion of LiPON is small, there are fewer lithium ion transmission channels in the modified solid electrolyte, making the rate performance of Example 7 worse than that of Example 5. Comparative Example 1-No A added The method described in Example 1 was followed, except that the composite material (LiMn 0.6 Fe 0.4 PO4@[0.992LIPON•0.008Nb]) in different proportions. The assembly of lithium-ion button half-cell is the same as in Example 1.
[0074] Characterization test: LiMn can be obtained by scanning electron microscopy test 0.6 Fe 0.4 The primary particle size of PO4@[0.992LIPON•0.008Nb] is 138 nm. The specific surface area is 15.8 m 2 / g, XRD shows that the diffraction peak of the composite material corresponds well to the lithium iron manganese phosphate standard card, indicating that the modified solid electrolyte does not change the crystal structure of lithium iron manganese phosphate.
[0075] The capacity retention rate of 100 cycles and the capacity retention rate of 2C relative to 0.1C are recorded in Table 1. Since there is no A in the modified solid electrolyte in the control group, the existence of LiPON alone makes its stability poor, so that the discharge specific capacity decay in the cycle of Comparative Example 1 is faster than that in Example 1.
[0076] Comparative Example-2-No M added The method described in Example 1 was followed, except that the composite material (LiMn 0.6 Fe 0.4PO4@[0.2C•0.8LIPON]) in different proportions. The assembly of lithium-ion button half-cell is the same as in Example 1.
[0077] Characterization test: LiMn can be obtained by scanning electron microscopy test 0.6 Fe 0.4 The primary particle size of PO4@[0.2C•0.8LIPON] is 127 nm. The specific surface area is 16.2 m 2 / g, XRD shows that the diffraction peak of the composite material corresponds well to the lithium iron manganese phosphate standard card, indicating that the modified solid electrolyte does not change the crystal structure of lithium iron manganese phosphate.
[0078] The capacity retention rate of 100 cycles and the capacity retention rate of 2C relative to 0.1C are recorded in Table 1. Since there is no M in the modified solid electrolyte in Control Group 2, the rate performance of Comparative Example 2 is worse than that of Example 1.
[0079] The parameter settings of the above embodiments and comparative examples are shown in Table 1 below: Table 1 Measurement data of examples and comparative examples
[0080] As can be seen from Examples 1 to 5 in Table 1 above, the battery prepared using the components defined in this application has good cycle performance. As can be seen from Examples 4 and 5, the preferred range of the molar ratio of A in the modified solid electrolyte is 0.1-0.4, and the comprehensive performance of the battery within the above range is more excellent. As can be seen from Comparative Examples 1 and 2, A is conducive to improving the cycle stability of the battery, and M is conducive to improving the rate performance of the battery.
[0081] Other structures and operations of the positive electrode materials, positive electrode sheets, batteries and electrical equipment according to the embodiments of the present invention are known to those skilled in the art and will not be described in detail here.
[0082] In the description of the present invention, it should be understood that the terms "center", "longitudinal", "lateral", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", "clockwise", "counterclockwise", "axial", "radial", "circumferential" and the like indicate orientations or positional relationships based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the referred device or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as limiting the present invention.
[0083] In the description of the present invention, "plurality" means two or more.
[0084] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "illustrative embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials, or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example.
[0085] Although the embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the claims and their equivalents.
Claims
1. A positive electrode material, characterized in that: include: An active material and a modified solid electrolyte, wherein the modified solid electrolyte is wrapped on the outer surface of the active material, and the chemical formula of the modified solid electrolyte is xA·(1-xy)LIPON·yM, wherein A includes at least one of C, Si, SiC and GaN, and M includes at least one of Mg, Ti, Mo, La, Nb, V and Te.
2. The positive electrode material according to claim 1, characterized in that The M includes at least one of Ti, Mo and Nb.
3. The positive electrode material according to claim 1, characterized in that The x satisfies: 0<x<1; and / or, The y satisfies: 0.0001<y<0.
03.
4. The positive electrode material according to claim 3, characterized in that The x further satisfies: 0.1<x<0.4; and / or, The y further satisfies: 0.0005<y<0.
02.
5. The positive electrode material according to claim 1, characterized in that The primary particle size of the positive electrode material is D1, and the specific surface area is S, wherein D1 and S respectively satisfy: 0.1 μm ≤ D1 ≤ 10 μm, 0.5 μm 2 / g≤S≤18m 2 / g.
6. The positive electrode material according to claim 1, characterized in that The thickness of the modified solid electrolyte wrapped on the active material is W, wherein W satisfies: 1 nm ≤ W ≤ 20 nm.
7. The positive electrode material according to any one of claims 1 to 6, characterized in that The active material includes at least one of lithium iron manganese phosphate, lithium iron lithium oxide, ternary material, lithium-rich manganese, lithium manganate, lithium cobalt oxide, lithium vanadium phosphate and lithium nickel oxide.
8. A positive electrode sheet, characterized in that: include: current collector; A positive electrode material layer is formed by applying the positive electrode material according to any one of claims 1 to 7 on at least one side surface of the current collector in the thickness direction.
9. A battery, characterized in that: It comprises the positive electrode material according to any one of claims 1 to 7, or the positive electrode sheet according to claim 8.
10. An electrical device, characterized in that: Comprising a battery according to claim 9.